(untitled) (American & British Studies Annual, 2011)
Feminine subjectivity in Bollywood films is constructed by film-makers and by the demand of audience fantasies as a miraculous mixture of contradictions. Is this traditional or transnational? Female constructs such as Gauri (the protagonist of Lagaan) expose traditional dichotomies deeply embedded in Indian culture. Women aspire to be powerless victimized women and powerful goddesses at the same time. Naturally, when a nationalist discourse shapes the images the feminist critic cannot but protest that such iconography degrades women by presenting them in simplistic oppositions. Yet, the feminist Amrita Basu observes that local women of power speak from positions of moral superiority conditioned by their chastity, and they represent no challenge to patriarchal values (Basu 1988). The image of Gauri in Lagaan seems to be the product of a similar schizophrenia, and gendered constructs of Indian vision (like Gauri) tend to be perceived as schematic creations of anticolonial nationalism, yet echoing transnational gender policies. Moreover, the film operates in a Neo-Victorian setting, examining the heritage of colonial pressures in post-colonial times. This setting allows for specific cultural, historical and political conditions to be delineated in the present, including a possible re-evaluation of gender roles in the third world. The cultural production of Bollywood emphasises the notion of reclaiming Indian women, who are constructed to resemble Sita or Radha in Indian mythology (Mishra 2002). Finally, Bollywood imagery supposedly becomes transnational (Thomas 1985). Lagaan shows the problematic accounts of official colonial history, and it allows the rediscovery of suppressed personal histories via constructs of memory, fantasy, narrative and myth.